STEYN, Daniël Wynand [Danie] Inventory of documents - STEYN, Daniël Wynand [Danie] (ARCA, 2018)
[1980-1982], Minister of Education and Training [1982-1983], Mineral and Energy affairs [1983-1986], Economic Affairs and Technology [1986-1989].
COVERAGE 1964-1981; 22 Files; 0,55 Metres.
Keywords: STEYN, Daniël Wynand [Danie]; Inventories; Politicians; National Party